Development and clinical validation of an LC–MS/MS method for the quantification of pazopanib in DBS. (January 2016) - Verheijen, Remy B; Bins, Sander; Thijssen, Bas; Rosing, Hilde; Nan, Lianda; Schellens, Jan HM; Mathijssen, Ron HJ; Lolkema, Martijn P; Beijnen, Jos H; Steeghs, Neeltje; Huitema, Alwin DR
Background: Pazopanib is approved for the treatment of renal cell carcinoma and soft tissue sarcoma. Analyses show increased benefit in patients with plasma trough concentrations ≥20.5 μg/ml compared with patients with lower concentrations.Methods & results: We developed a DBS assay as a patient friendly approach to guide treatment. The method was validated according to US FDA and EMA guidelines and European Bioanalysis Forum recommendations. Influence of spot homogeneity, spot volume and hematocrit were shown to be within acceptable limits. Analysis of paired clinical samples showed a good correlation between the measured plasma and DBS concentrations (R 2 of 0.872).Conclusion: The method was successfully validated, applied to paired clinical samples and is suitable for application to therapeutic drug monitoring of pazopanib.